KOMPARASI HUKUM ISLAM DENGAN UU NO. 4 TAHUN 1979 TENTANG HAK ANAK - Ulya Sofiana (istinbath, 2013)
Children need protection not only because they are weak but also because they are the next potential generation. Since they are not yet able to fulfill their own needs and to protect themselves from dangers, they need helps from others in realizing their rights. As a young generation, they deserve mental and physical well-beings to ensure their growth. Based on analyses of various theories and references, this study seeks to examine and compares the Law of Child Welfare No. 4/1974, especially Article 2, and Islamic law regarding children’s welfare and rights. This study finds that Islamic law has a more comprehensive rule on children’s rights and well-being than that of the positive law. Islamic law, for example, stipulates that children deserve early care and protection even when they are still in their mother’s womb.